Enhancement of the transverse stress tolerance of REBCO Roebel cables by epoxy impregnation. (30th April 2015) - Otten, S; Dhallé, M; Gao, P; Wessel, W; Kario, A; Kling, A; Goldacker, W
Abstract: RE BCO Roebel cables are considered for application in high-temperature superconducting inserts for accelerator magnets because of their fully transposed geometry, high-engineering current density, and adequate bending tolerance. In these magnets the cables experience Lorentz forces leading to transverse stresses up to 100–150 MPa. Previous reports have shown bare Roebel cables to degrade under such high stresses so that additional reinforcement is required. In this work, two identical Roebel cables are vacuum impregnated with a mixture of epoxy and fused silica in order to improve their tolerance to transverse stress. After impregnation, the critical current of the cables is measured under transverse mechanical loading at T = 4.2 K, T. A reference cable without impregnation is tested as well. Pressures up to 350 MPa are applied to a short (30 mm) section of each cable. No degradation was observed for pressures up to 250 MPa and 170 MPa in the two impregnated cables. The critical current of the non-impregnated cable, in contrast, started to decrease at stresses as low as 40 MPa.